Adapt locally and act globally: strategy to maintain high chemoreceptor sensitivity in complex environments - Lan, Ganhui; Schulmeister, Sonja; Sourjik, Victor; Tu, Yuhai (Molecular systems biology, 2011)
In bacterial chemotaxis, several types of ligand-specific receptors form mixed clusters, wherein receptor?receptor interactions lead to signal amplification and integration. However, it remains unclear how a mixed receptor cluster adapts to individual stimuli and whether it can differentiate between different types of ligands. Here, we combine theoretical modeling with experiments to reveal the adaptation dynamics of the mixed chemoreceptor cluster in Escherichia coli. We show that adaptation occurs locally and is ligand-specific: only the receptor that binds the external ligand changes its methylation level when the system adapts, whereas other types of receptors change methylation levels transiently. Permanent methylation crosstalk occurs when the system fails to adapt accurately. This local adaptation mechanism enables cells to differentiate individual stimuli by encoding them into the methylation levels of corresponding types of chemoreceptors. It tunes each receptor to its most responsive state to maintain high sensitivity in complex environments and prevents saturation of the cluster by one signal.
Gesehen am 12.07.2022